Effects of ATP-sensitive Potassium Channels on the Expression of P21, P27 and Leptin - 王曜晖 郑海燕 刘声远 (Journal of Huazhong University of Science and Technology. Medical sciences, 2009)
This study investigated the effects of ATP-sensitive potassium channels on the expression of P21, P27 and leptin. The expression of receptor of ATP-sensitive potassium channels （sulphonylurea receptor, SUR） mRNA in the preadipocytes and leptin mRNA was detected by PCR after rat preadipocytes were treated with the opener （diazoxide） or inhibitor （glibenclamide） of ATP-sensitive potassium channels during the process of inducing differentiation. The expression of P21 and P27 in preadipocytes treated with diazoxide or glibenclamide was assayed by Western blot. The results showed that the expression of SUR2, not SUR1 was detected in adipose tissue, preadipocytes and adipocytes. Alter treatment of preadipocytes with diazoxide, the expression levels of P21 and P27 were obviously higher than glibenclamide-treat ed group those in control group, but the were lower than those in control expression levels of P21 and P27 in group. During the process of inducing differentiation, the expression of leptin mRNA in preadipocytes treated with diazoxide was increased greatly, but the expression of leptin mRNA in glibenclamide-treated group decreased obviously. It was concluded that ATP-sensitive potassium channels might be involved in the proliferation and differentiation of rat preadipocytes by changing the expression of P21, P27 and leptin.